2017
DOI: 10.1021/acs.analchem.7b00741
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Collision Cross-Section Values for Small Molecules: Application to Pesticide Residue Analysis

Abstract: The use of collision cross-section (CCS) values obtained by ion mobility high-resolution mass spectrometry has added a third dimension (alongside retention time and exact mass) to aid in the identification of compounds. However, its utility is limited by the number of experimental CCS values currently available. This work demonstrates the potential of artificial neural networks (ANNs) for the prediction of CCS values of pesticides. The predictor, based on eight software-chosen molecular descriptors, was optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
161
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(166 citation statements)
references
References 35 publications
(47 reference statements)
4
161
1
Order By: Relevance
“…For this purpose, in-silico fragmentation matching [18,19] and prediction of retention time (RT) have been shown to reduce the list of potential compounds [1,20]. In-silico prediction of CCS and IMS drift times have utilized molecular modelling techniques [21][22][23]; however, models based on molecular descriptors have shown similar results while drastically reducing computing time [24][25][26][27], which corresponds to findings for prediction of the reduced ion mobility constants [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, in-silico fragmentation matching [18,19] and prediction of retention time (RT) have been shown to reduce the list of potential compounds [1,20]. In-silico prediction of CCS and IMS drift times have utilized molecular modelling techniques [21][22][23]; however, models based on molecular descriptors have shown similar results while drastically reducing computing time [24][25][26][27], which corresponds to findings for prediction of the reduced ion mobility constants [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The substantial challenge of exposomic studies, where 1000s of compounds including xenobiotics, secondary metabolites, and transformation products that remain currently unidentified, is a focus of high‐throughput IM–MS studies whereby computational prediction of CCS values is suggested to be a way forward to allow rapid screening of samples . Such a workflow requires substantial computational effort to predict CCS values, but some authors have presented promising results using different approaches in addressing this major challenge . The workflow demonstrated by Zhou et al.…”
Section: Application Of Ion Mobility Spectrometry To the Analysis Of mentioning
confidence: 99%
“…The workflow demonstrated by Zhou et al. was particularly in‐depth as DTIMS experimental data from a total of ∼400 compounds were used to generate molecular descriptors to train a machine‐learning algorithm, which matched CCS values measured on their instrument with a median relative error of 3%. Alternative approaches to modeling of CCS are discussed in Section .…”
Section: Application Of Ion Mobility Spectrometry To the Analysis Of mentioning
confidence: 99%
See 2 more Smart Citations